2014
DOI: 10.17554/j.issn.2224-3992.2014.03.474
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Irritable Bowel Syndrome and Shift Work: Prevalence and Associated Factors Among Nurses

Abstract: AIM: Irritable Bowel Syndrome (IBS) is commonly seen in the general population. Mechanisms proposed as the underlying pathogenesis include visceral hypersensitivity, alteration in bowel motility, psychological status and abnormal intestinal barrier. It has been observed that circadian rhythms and sleep are altered by shift work, which may ultimately increase stress and worsen health problems. The aim was to determine the prevalence of IBS among nurses and evaluate the relationship between shift work and IBS. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…IBS is estimated to have a world-wide prevalence of 10–15% ( Canavan, West & Card, 2014 ; Sperber et al, 2017 ). Prevalence rates of IBS are typically higher among nurses, with rates ranging from 17.4% in China ( Liu et al, 2014 ) to 45.2% in Nigeria ( Akere & Akande, 2014 ). The prevalence rate of IBS among study participants was 35%, quite similar to the prevalence rate reported among nurses at the University of Michigan Medical Center (36.6%) ( Nojkov et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…IBS is estimated to have a world-wide prevalence of 10–15% ( Canavan, West & Card, 2014 ; Sperber et al, 2017 ). Prevalence rates of IBS are typically higher among nurses, with rates ranging from 17.4% in China ( Liu et al, 2014 ) to 45.2% in Nigeria ( Akere & Akande, 2014 ). The prevalence rate of IBS among study participants was 35%, quite similar to the prevalence rate reported among nurses at the University of Michigan Medical Center (36.6%) ( Nojkov et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…16 On the other hand, other studies among Nigerian medical student and nursing staff were consistency with some studies in Asia where the prevalence of IBS was as high as 26.1% and 45.2% in that order. 17,18 The pathophysiology behind a high prevalence of IBS in medical students is constant nerve-racking environment to meet deadlines, examinations anxiety, long working and studying hours and less hours of sleep. 9 Nevertheless, health care professionals are subjected to stressful environment due to the nature of the work and working environment.…”
Section: Discussionmentioning
confidence: 99%
“…22 In African studies findings were similar to Pakistan, Japan and China where IBS-M was predominant (19.6% and 60.7%). 16,18 IBS has been shown to be associated with several factors as stipulated in literature review. In this study female gender, age below 25years, alcohol intake and finalist students were independent predictors of IBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation